Studi Eksperimen PENGARUH PENGGUNAAN MEDIA KONKRET PADA MATERI TUMBUHAN TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS 4 SD DI KABUPATEN CIREBON: Penggunaan Media Konkret untuk Meningkatkan Keterampilan Proses Sains Siswa Sekolah Dasar - Dewika, Erna Dewika; Mikkey Anggara Suganda; Fanni Zulaiha (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2026)
The results of the observation show that the science process skills of fourth-grade students at SDN 1 Suranenggala have not developed optimally. This is due to the lack of use of concrete media, causing students to be less actively involved in the learning process. Therefore, concrete media as a visual aid is considered an effective solution because it provides direct learning experiences that are easier for students to understand. This study aims to determine the effect of using concrete media on the plant material toward the science process skills of fourth-grade students. The research type is a quasi-experimental design with a population of all fourth-grade students at SDN 1 Suranenggala, and the sample consisted of 29 students from class IV A. The instruments used were multiple-choice tests on science process skills and observation sheets. The instruments were tested for validity and reliability using IBM SPSS Statistics 30. Of the 16 test items, 10 were declared valid because the calculated r-value was greater than the r-table. The reliability test results showed r-count > r-table, namely 0.659 and 0.665 > 0.344, indicating that the instruments were reliable. The findings revealed that the use of concrete media had a significant effect on science process skills. Based on the paired sample t-test, the significance value was 0.001 < 0.05, indicating a significant effect. The average N-gain score for the experimental class was 0.4792 (medium category) and 0.2685 (low category) for the control class. Thus, it can be concluded that the use of concrete media on plant material is effective in improving the science process skills of fourth-grade students at SDN 1 Suranenggala, Cirebon Regency.